La Digitalizzazione al centro del progetto di ricostruzione della Cattedrale di Notre-Dame - Patrimoine, ArtGraphique (Archeomatica, 2022)
Art Graphique & Patrimoine, pioneer of new technologies and expert in cultural heritage, has joined the "Etablissement public" in charge of the conservation and restoration of Notre-Dame and the CNRS - National Center for Scientific Research - in the context of the creation of the " digital twin "of the cathedral. In March 2021, two years after the fire that destroyed the medieval roof and trusses, AGP completed its work on the digital Notre-Dame project.